Redescription of three species of Anastrepha (Diptera, Tephritidae) rediscovered in Brazil, with the establishment of a new synonym - Uramoto, Keiko; Zucchi, Roberto A.; Norrbom, Allen L. (Zootaxa, 2015)
The descriptions of Anastrepha matertela Zucchi and A. tenella Zucchi were based exclusively on the holotypes (female). Based on additional specimens collected in Brazil since their original descriptions, both species are redescribed and illustrated. A lectotype is designated for Anastrepha bivittata (Macquart, 1843), which also is redescribed and considered to be the senior synonym of A. fumipennis Lima, 1934.